POLYMORPHISMS AND ALLELE FREQUENCY OF BMPR1B GENES IN LOCAL AWASSI SHEEP - A. H. Essa; T. R. Mohammed; N. N. Al-Anbari (مجلة الأنبار للعلوم الزراعية, 2025)
This study aimed at uncovering the polymorphisms in the BMPR1B gene from the blood samples of 35 Awassi ewes at the Roundabout Agricultural Research Station - Anbar Governorate. DNA was extracted from blood samples which were tested using PCR by adopting the gene primer. Single nucleotide polymorphism (SNP) technology was used to determine the occurrence of variations for the specific alleles of each ewe. The results showed that the genotype and allele frequencies of four loci of the BMPR1B gene were significantly different (P≤0.01). The first position of rs410310346 (T > C) showed three genotypes i.e., TT, TC and CC, with percentages of 2.56, 26.88 and 70.56%, respectively, and the allelic frequency of the T alleles were - 0.16 and C - 0.84. For the second position of rs592447725 (G > A(, three genotypes appeared as GG, GA, and AA at percentages of 72.26, 25.50, and 2.24%, respectively, and an allelic frequency of G 0.85 and A 0.15. For rs429006240 (T>C) the three genotypes of TT, TC and CC had percentages of 92.16, 7.68 and 0.16%, respectively, with a T allele frequency of 0.96 and C - 0.04. The fourth locus rs419457334 (G>C) showed three genotypes GG, GC, and CC with the percentages of polymorphism at 77.44, 21.12, and 1.44%, respectively and the allelic frequency of G was 0.88 while that of C was 0.12. The results show the allelic frequency in the BMPR1B gene for four positions having polymorphisms (CC, GG, TT, and GG) that were superior to the other genotypes carried by the Awassi ewes